Effect of Fe2+ on Akimotoite to Bridgmanite Transition: Its Implication on Subduction Dynamics - Pandit, Priyanka; Chandrashekhar, Prathibha; Sharma, Sparsh; Shukla, Gaurav (Geochemistry, geophysics, geosystems : G3, 2025)
Seismic studies in cold subduction zones indicate several discontinuity structures near the 660‐km boundary. Studies indicate that the akimotoite to bridgmanite transition may play a significant role in unraveling the complexity of this region. In this study, we used first‐principles methods to explore the stability field of iron‐rich analogs of akimotoite and bridgmanite (Mg1−xFex2+SiO3 $\left(Mg_{1-x}Fe_{x}^{2+}\right)SiO_{3}$ under high‐pressure‐temperature conditions. The Fe2+ inclusion significantly reduces the phase transition pressure. Overall, our calculated phase boundary and thermoelastic properties compare well with the available results from previous studies. The onset transition pressure and the width of the two‐phase field exhibit a clear dependence on iron concentration, with the width of the two‐phase field increasing as iron concentration increases. Our results indicate that the relatively high Fe2+ (∼x = 0.5) found in natural Fe analogs of akimotoite and bridgmanite would not be possible under mantle transition conditions. However, Fe2+ incorporation relevant for mantle composition (<10 mol.% FeO) may explain the slab stagnation above 660 km depth as well as seismically observed trends of velocity perturbations in the slabs of the northwest Pacific region around ∼500–600 km depth. Plain Language Summary The 660‐km discontinuity is quite fascinating due to its unique features in various cold subduction zones. The subducting slabs generally exhibit different kinds of phase assemblages and different phase transition paths due to their colder nature compared to the surrounding mantle. Harzburgite composition, which is gravitationally more stable around the lower transition mantle zone in subducting slabs, can contain up to 15 vol% akimotoite. As observed in experimental studies, the akimotoite to bridgmanite phase transition seems to play an important role in complex discontinuities in subduction slabs. The discovery of iron‐rich natural analogs of akimotoite and bridgmanite in Suizhou L6 chondrite, now known as hemleyite and hiroseite, respectively, has sparked interest in FeO solubility in the system at relevant pressure and temperature conditions. We calculated thermodynamic and thermoelastic properties with increasing iron concentrations in these minerals to understand their stability field. Our estimated phase boundaries and elastic properties compare well with previous results. Simulations suggest that the Fe2+‐bearing akimotoite to bridgmanite transition in the lower mantle transition zone might be responsible for subducting slabs to become stagnant above 660 km depth, causing seismic perturbation in the southern Kurile, northern Bonin, and Honshu regions. Key Points The natural Fe analogs of akimotoite and bridgmanite with ∼50% Fe2+ may not be stable at the mantle transition condition The addition of Fe2+ reduces transition pressure and may be responsible for slab stagnation above the 660 km discontinuity Compressional and shear velocity contrast at the transition increases with Fe2+ incorporation